Modelling bargaining behaviors within biotech clusters - Towards the "power of the weak" emergence? - Isabelle Leroux; Alain Berro (European Regional Science Association (ERSA), 2005)
If spatial and industrial economics theorical models, such as industrial districts, clusters, or learning regions propose a large analysis of differentiated coordination mecanisms, it however not really takes into account behavior of dispute dynamics, such as conflict of bargaining and power, which can explain both diversity and ambivalence of local coordinations. So, our purpose in this contribution is to bring to light that bargaining and power conflicts are at stake in coordinations structuration within territories. We base this contribution on Artificial Life simulations involving public and private local actors who bargain to share a local resource using more or less sophisticated strategies. On a methodologic point of view, our thought is based on an empirical established fact. Analysis of a biotechnology cluster in Toulouse-France (Leroux I., 2002, 2004) indeed contributes to bring to light that coordinations involving pharmaceutical industry, local communities and local research laboratories are based on direct or indirect evolving domination and concession bargaining games. If industrial firms play "the power of the weak" game, making concession of their decision power to public research laboratories, they endeavour systematically to exerce an influence or a discrimination power, by using hided and indirect means that forward by local communities.Starting from this established fact, we propose Artificial Life simulations of local bargaining games, inspired from the T. Ellingsen (1997) bargaining evolutionnary game. This is a Nash demand game under ultimatum. It leads to the interaction of obstinate agents whose demands are independent of those of the adversaries, and sophisticated agents who adapt their demand to that hoped for of their adversaries rather than gain nothing. As a result, our simulations show that bargainings between these local actors lead to an agreement which is not a perfect share, or an "universal" rule, but a compromise frequently hiding complex mecanisms of domination and concession. The main contribution of these simulations, which are based on genetic algorithms, is to put in a prominent position the variations of behavioral rules. We show how bargaining is an evolving processus based on domination and concession behaviors (influence, coercion,…) bringing to light the T. Schelling (1960) "power of the weak". This result brings to the fore the question of flexibility and phasing dynamics of power behaviors in local coordination bargainings. This model can contributes to open new researches focused on power and conflict strategies within local coordinations.
Keywords: 330